Forensic Psychiatrists - Lederman, Lynne (MD Conference Express, 2015)
Forensic psychiatrists face ethical issues as they balance legal and therapeutic concerns. Accurate assessments of risk are important in many therapeutic situations, including counseling victims of stalking, determining whether juveniles will offend or reoffend, preventing inpatient suicide, and evaluating future dangerousness at sentencing hearings in death penalty cases.